Yield gap, profitability and inefficiency of Aman rice in coastal areas of Bangladesh - Roy, AC; Rahman, MA; Khan, MA (Progressive Agriculture, 2020)
Despite of being an extremely overpopulated country with a limited land resource, Bangladesh has managed to increase its food production to a viable level. Yet it is necessary to increase production of food crop in order to cope with the growing population in a sustainable way. Closing yield gap is a means of attaining sustainability of agricultural intensification to keep pace with the growing crop demand. The objective of the present study is to assess the inefficiency and the yield gap of Aman rice production in climate vulnerable areas in Bangladesh. The study was conducted in Shaymnagar and Kaliganj Upazilas of Satkhira district in Bangladesh and data were collected using a stratified random sampling technique from 110 Aman cultivating farmers. Descriptive statistical techniques as well as Stochastic Frontier model were used to achieve the objectives of the study. The study revealed that, Aman rice cultivation was profitable in the study area. We estimated the model based yield gap, highest recorded yield gap and experimental yield gap. The mean efficiency analysis revealed that farmers could increase their production with optimal use of inputs and proper management systems. Absence of proper knowledge about the optimum input use and lack of institutional training as well as inadequate extension services were responsible for the reduced yield in most farmers’ fields. Salinity has reduced the overall productivity of the region, but it is believed that by popularizing the practice of saline tolerant rice variety and addressing the above mentioned issues the potential production can be achieved in the coastal region. Progressive Agriculture 30 (4): 395-404, 2019